2015
DOI: 10.1590/1678-775720150170
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and bioactivity of calcium silicate-based endodontic sealers in human dental pulp cells

Abstract: Mineral Trioxide Aggregate (MTA) is a calcium silicate-based material. New sealers have been developed based on calcium silicate as MTA Fillapex and MTA Plus. Objective The aim of this study was to evaluate biocompatibility and bioactivity of these two calcium silicate-based sealers in culture of human dental pulp cells (hDPCs).Material and Methods The cells were isolated from third molars extracted from a 16-year-old patient. Pulp tissue was sectioned into fragments with approximately 1 mm3 and kept in supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 26 publications
3
44
0
5
Order By: Relevance
“…The difference is considered to be caused by the constant Ca/P ratio in the synthesis. According to the cell parameter results obtained by Rietveld refinement of the XRD data (Table 1), the lattice cell parameters of Zn-HA continue to decrease with substitution of Zn 2+ ions increasingly getting into the apatite structure, following the trend described by other works [8]. It makes sense that both the a - and c -axes decreased with Zn substitution since the size of Zn 2+ ions (0.074 nm) is smaller than that of Ca 2+ (0.099 nm).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The difference is considered to be caused by the constant Ca/P ratio in the synthesis. According to the cell parameter results obtained by Rietveld refinement of the XRD data (Table 1), the lattice cell parameters of Zn-HA continue to decrease with substitution of Zn 2+ ions increasingly getting into the apatite structure, following the trend described by other works [8]. It makes sense that both the a - and c -axes decreased with Zn substitution since the size of Zn 2+ ions (0.074 nm) is smaller than that of Ca 2+ (0.099 nm).…”
Section: Resultssupporting
confidence: 67%
“…Previous studies have reported that Zn-HA has favourable effects on reducing inflammation and improving monocyte chemotaxis [11]. Additionally, zinc ion promotes the anabolic effects of insulin-like growth factor-I (IGF-I) in MC3T3 osteoblastic cells by increasing both the alkaline phosphatase activity and protein concentration [8, 12], due to the fact that the zinc binding protein metallothionein plays an important role in the regulation of cell cycle and differentiation [13]. Not only can zinc promote osteoblast proliferation and differentiation, but it has also shown an inhibitory effect on osteoclastic bone resorption [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the experiment, MTT assay was used, which involves the measurement of mitochondrial activity of succinate dehydrogenase, thus informing about the proper functioning of the cultured cells [6, 15, 17, 19, 24]. Although the technique is simple, it is sufficiently precise and allows for obtaining quick results.…”
Section: Discussionmentioning
confidence: 99%
“…, Mestieri et al . , Zhou et al . ), whilst Endoseal MTA (EndoSeal, Maruchi, Seoul, Korea), a new sealer without resin, had lower cell viability than ProRoot (PMTA; Dentsply, Tulsa, OK, USA) (Lim et al .…”
Section: Introductionmentioning
confidence: 99%